Factors Affecting Profit Management with Corporate Governance as Moderating Variable - Hendang Tanusdjaja; Justin Justin (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to determine the influence of company size, financial distress, and leverage on profit management moderated by corporate governance. The sample used in this research was taken by purposive sampling method from companies listed on the IDX during 2018-2020. The data is secondary data and processed using SPSS version 25 and Microsoft Excel 2019. Based on the criteria, 54 companies were selected that could be used as samples. The total number of data is 162 minus 40 outlier data so that the amount of data that can be used is 122 data and then tested with multiple linear regression analysis technique. Based on the research conducted, company size and financial distress have a significant positive influence on profit management, while leverage has no influence on profit management. Corporate governance with independent commissioners as a proxy cannot moderate company size and financial distress, but can moderate the relationship between leverage and profit management.